Transformation of Political Culture in Post-Independent Sri Lanka: Conceptual and Empirical Overview - Vitharana, Sarath; Abeysinghe, Chaminda (Technium Social Sciences Journal, 2021)
The study examined the concept of political culture especially in relations to meaning, it found out the historical development of political culture and identified factors affecting the formation of political culture in post-independent era in Sri Lanka. Secondary data and content analysis were adopted by the study as method of data collection. The study found that, the formation and transformation of political culture in Sri Lanka mainly followed prevailing political institutions and provisions throughout the entire political history of the country. It also found that, the transformation of political culture in independent Sri Lanka is basically determined by pre and post government and political reforms introduced by British rule and local leaders. Social, cultural and economic factors which came in the post independent era in the country as the study observed, also contributed to the formation of political culture in the country. The study concluded that, political culture during pre-independent era has significantly transformed into a different level mainly due to the political, institutional and procedural changes.